Co-encapsulation of magnetic nanoparticles and cisplatin within biocompatible polymers as multifunctional nanoplatforms: synthesis, characterization, and in vitro assays. (8th January 2018) - Ibarra, Jaime; Encinas, David; Blanco, Mateo; Barbosa, Silvia; Taboada, Pablo; Juárez, Josué; Valdez, Miguel A
Abstract: In this work, we report the synthesis, characterization and biological evaluation of a multifunctional hybrid biocompatible nanoplatform consisting of a biodegradable poly(lactic-co-glycolic acid) (PLGA) matrix functionalized with a polyvinyl alcohol/chitosan mixed surface layer, and co-loaded with superparamagnetic iron oxide nanoparticles (SPIONs) and the anticancer drug cisplatin. In this manner, problems associated with cisplatin low aqueous solubility are precluded as well as a sustained controlled release of the drug is obtained. The hybrid nanoplatforms displayed slightly positive charges and spherical shapes, with an average diameter of ca 100 nm and very low polydispersity. This size range makes these particles suitable a priori to avoid extensive macrophage recognition whilst ensures exploitation of passive targeting in tumoral cells by the enhanced permeation and retention effect and successful interaction with cell surfaces. SPIONs and drug loading extents were determined by inductively coupled plasma mass spectrometry and UV–vis absorption spectroscopy, respectively. The presence of the magnetic nanoparticle in the hybrid platform should enable their intended use as T2 imaging contrast agents as denoted from magnetic imaging measurements in vitro . Furthermore, in vitro release profiles of cisplatin from nanoplatform showed an initial burst release of about 16% in the first 6 h, followed by a sustained release over 10 days ensuring a slow delivery of the drug in the site of action to enhance chemotherapeutic activity. This was confirmed by in vitro cytotoxicity assays denoting that the chemotherapeutic effect of cisplatin on both cervical HeLa and breast MDA-MB-231 cancer cell lines is largely improved when encapsulated in the nanoplatform. Thus, the present characterization and in vitro biological evaluation data indicate that this nanoplatform can be considered as a promising theragnostic nanoplatform for combined imaging and therapy of several tumors. Moreover, its design using different biocompatible materials approved by regulatory agencies might open further expectatives to clinical translation once performing additional in vivo experiments currently on development.